Clinical and morphological changes in the kidneys in patients with pulmonary tuberculosis - Ergashov Behruzjon Komilovich (Journal of Innovation in Education and Social Research, 2025)
To develop the mechanism of development of concomitant diseases in the kidneys in patients with pulmonary tuberculosis and the concept of clinical and morphological changes in the kidneys.